Behavioral Adaptations of Nocturnal Primates in Fragmented Forests (Zoological Archives: An International Journal, 2022)
Nocturnal primates -- including galagos, lorises, pottos, mouse lemurs, dwarf lemurs, aye-ayes, and tarsiers -- represent the ancestral primate condition and collectively comprise over 140 species spanning sub-Saharan Africa, South and Southeast Asia, and Madagascar. Their cryptic, solitary, and low-density ecology makes them exceptionally vulnerable to habitat fragmentation yet poorly monitored relative to diurnal primate counterparts. This study quantified behavioural adaptations across 24 nocturnal primate species at 84 field sites spanning a forest fragment size gradient from 0.4 to 48,000 hectares across Madagascar, Borneo, and West Africa, using a standardised protocol combining line transect distance sampling, radio-telemetry of 247 GPS-collared individuals, and arboreal camera trapping (847 camera-nights). Home range area increased by mean +184.7% in fragments < 100 ha compared with intact forest controls, reflecting increased ranging effort to compensate for reduced local resource density. Diet breadth expanded significantly in small fragments (Shannon H index +0.84 +- 0.28; p < 0.001), driven by opportunistic use of cultivated and non-native food plants at fragment edges. Activity patterns shifted toward earlier activity onset (mean -47.4 minutes relative to sunset in fragments < 10 ha; p < 0.001) and reduced overall activity budget (-18.4% active hours; p < 0.01), consistent with elevated predation pressure and food search costs at fragment edges. Population density declined exponentially with fragment area (r2 = 0.84; p < 0.001), with a critical threshold at approximately 50 ha below which mean density fell below the estimated minimum viable population density for most study species. These results identify small forest fragments (< 50 ha) as functionally inadequate for nocturnal primate population persistence and quantify the magnitude of behavioural compensation required in larger fragments that remains energetically costly.